Gastropods from the Norian (Late Triassic) Nayband Formation near Natanz (Iran) - Nützel, Alexander; Aghababalou, B.; Senowbari-Daryan, Baba (Bulletin of Geosciences, 2012)
A collection of marine gastropods from the Late Triassic (Norian) Nayband Formation of Iran near Isfahan consists of 207 specimens representing 9 species (3 species are new). Rarefaction analyses and diversity indices indicate that the diversity of the studied fauna is much lower than that from the vicinity of Ali Abad (Tabas region) and somewhat less diverse than that of Dizlu (Isfahan region). All known gastropod faunas from the Nayband Formation are dominated by more or less high-spired caenogastropods. However, species composition and rank abundance of the most common taxa differ strongly in all three gastropod collections. The new species are Acilia? basistriata, Teutonica? natanzensis and Protorcula iranica. The present gastropod fauna is dominated by the caenogastropods Coelostylina conica, Protorcula iranica and Teutonica? natanzensis.
UnivIS-Import:2017-11-07:Pub.2012.nat.dgeo.IGM.LP.gastro
Keywords: Diversity; Gastropoda; Iran; Nayband formation; Taxonomy; Triassic